PELAKSANAAN AKAD WAKALAH DALAM PEMBIAYAAN MURABAHAH DI BANK SYARIAH MANDIRI KCP JATINANGOR - Febrianti Nurul Fadilah; Diah Siti Sa'diyah (Al-Muamalat: Jurnal Ekonomi Syariah, 2019)
ABSTRACT The implementation of the Wakalah contract in Murabahah Financing at BSM KCP Jatinangor Office in micro-financing products, namely where the bank fully surrenders the customers to customers appointed by the Bank as representatives of the Bank to purchase goods in accordance with agreements in the form of transferred funds posted in form of bank account in the name of the customer. The purpose of this study was to determine, 1) Implementation of wakalah contract in murabahah financing in BSM KCP Jatinangor, 2) Consideration of banks on the implementation of wakalah contract in murabahah financing at BSM KCP Jatinangor, and 3) Overview of Sharia Economic Law on the implementation of wakalah in murabahah financing at BSM KCP Jatinangor. This framework of thinking starts from must be done on the basis of liking by fulfilling the values of justice. As for the transaction, there must be terms and conditions that must be fulfilled in accordance with sharia principles, so as not to cause harm and harm to one party. The approach method used in this writing is descriptive method, which describes the objective conditions and analyzes the collected data. The type of data used in this study is qualitative. The technique used is by way of observation, interviews, literature studies that relate to this research. Based on the results of the study the authors conclude as follows: (1) Implementation of wakalah contract in murabahah financing in BSM KCP Jatinangor on this microfinance product to attract public interest in order to increase customer loyalty to banks considering BSM KCP Jatinangor was established in education. (2) Considering that the bank is not a provider of goods or shops, the bank hereby authorizes the customer to act as a representative of the bank to purchase goods according to specifications, conditions and prices approved by the Bank. (3) There appears to be negligence carried out by the Bank in the implementation of the Wakalah agreement in murabahah financing in BSM KCP Jatinangor Finally it can be concluded that the implementation of the wakalah contract in murabahah financing is in accordance with the Sharia Economic Law in terms of contract and principle. However, it is not fulfilled in principle, namely the principle of prudence by the Bank and customers who are not involved in financing.